Reproductive aspects of piranhas Serrasalmus spilopleura and Serrasalmus marginatus into the Upper Paraná River, Brazil - Agostinho,C. S. (2003)
Construction of the Itaipu Dam, 150 km downstream from Sete Quedas Falls, resulted in the drowning of that natural geographic barrier, with consequent invasion of Serrasalmus marginatus in the upper stream. This event was followed by the reduction in the abundance of the native species, S. spilopleura. Analyzes of reproductive activity these species revealed that in lotic waters S. marginatus had a very intense reproductive activity while activity of S. spilopleura was nil. This, probably made it possible for the invading species to occupy new environments into the Upper Paraná River, using the river as an entry port. In the 1987-1988 period there was a marked decline in reproductive activity of S. spilopleura reflecting the negative effects of its interaction with the invading species, S. marginatus. The assertiveness of S. marginatus in caring for its offspring and aggressiveness in establishing its feeding territory may be the determining factor for its competitive superiority over S. spilopleura, and consequently its success in colonizing the Upper Paraná River. In addition to the negative interference of S. marginatus, a possible recruitment failure of S. spilopleura could have benefited the colonization of the floodplain by the invader species.